A kecskerák (Astacus leptodactylus) előfordulása a Balatonban - Dancsa, Barbara; Simon, Brigitta; Kucserka, Tamás (GEORGIKON FOR AGRICULTURE, 2018)
Because of Aphanomyces astaci and Anguilla anguilla settlements species like Astacus Leptodactylus are forgotten but nowadays they are starting to spread again. Three native species of crabs are present in Hungary: Astacus astacus, Astacus leptodactylus and Astacus torrentium but you can also find Orconectes limosus. My purpose was to research Astacus leptodactylus which veryfied the multiplication of species in the coasts of Lake Balaton at Keszthely bay. We put out traps for a whole year with a total cought 209 crayfish, and one Spinnycheak Crayfish. During our research we measured the length of crayfishes’ bodies and scissors. We caught 910 cm long crabs in average, but the biggest was 18 cm long.
Keywords: Astacus leptodactylus; Balaton